Beyond Boundaries: Elevating Continuity of Care in Student-Run Free Clinics - Joseph Kessler; Leo Puhalla; Jessica Lee; Maham Alvi; Taliyah Borromeo; Alicia Bond (Journal of Student-Run Clinics, 2024)
We discuss the challenge of continuity of care in Student-Run Free Clinics (SRFCs) across the nation due to barriers of transportation, variation in care teams, communication, coordination, and improper utilization of resources. Discussion at the 2023 Society of Student-Run Free Clinic’s Annual Conference “Bridging the Gap” session with various medical schools and respective SRFCs allowed us to identify after-care teams as a common and effective modality to improve continuity of care. Patient-centered care is at the heart of SRFCs, and we strongly believe that communicating outside of clinic hours allows for effective longitudinal patient care. Such initiatives allow for improvements in health status via motivational interviewing, discussing medications, and addressing socioeconomic issues. Each clinic we consulted during this session had its individualized program focused on the same ideology. By instituting an after-care team, SRFCs can improve continuity of care while fulfilling the Triple Aim outlined by the Institute of Healthcare Improvement (IHI). Our perspective article emphasizes the importance of after-care teams to improve continuity of care and patient value in relation to the Triple Aim.